Decorin is an early CSF biomarker of Alzheimer's Aβ amyloidosis. (31st December 2021) - Jiang, Richeng; Smailovic, Una; Haytural, Hazal; Haret, Robert Mihai; Shevchenko, Ganna; Tijms, Betty; Gobom, Johan; Abelein, Axel; Johansson, Jan; Zetterberg, Henrik; Winblad, Bengt; Frykman, Susanne; et al.
Abstract: Background: Alzheimer's disease (AD) brains are characterized by extracellular amyloid‐beta (Aβ) deposition and autophagy dysregulation. Here we aimed at deepening the understanding of these brain pathologies and how they translate to the CSF using App knock‐in mice. Method: AD postmortem brain tissues and App knock‐in mouse models ( App NL‐F and App NL‐G‐F ) were used for autophagy characterization. The cerebrospinal fluid (CSF) from App knock‐in mice was analyzed by label‐free mass spectrometry (MS) and compared with previously reported CSF MS results from patients. The expression of decorin in the mouse brains was analyzed by immunohistochemistry and western blot. The autophagy‐activating effect of decorin was measured in the mouse primary neurons. Result: p62 and LC3 II levels were increased in App NL‐G‐F mice similar to the marked accumulation of p62 in AD brains. Several extracellular matrix (ECM) proteins, including decorin, were significantly increased in the CSF of both App NL‐F mice and amyloid‐positive/tau‐negative subjects with normal cognition. Decorin was decreased in parvalbumin‐positive interneurons but increased in choroideus plexus of App NL‐F mice, both of which correlated with Aβ pathology. Decorin‐treated mouse primary neurons exhibited lowered p62 and LC3 II levels. Conclusion: Autophagy is similarly inhibited in the brains of App NL‐G‐F mice and AD patients. The similar increase of decorin in CSF of App NL‐F mice and amyloid‐positive/tau‐negative subjects with normal cognition indicates a potential of decorin as an early biomarker of Aβ amyloidosis. In addition, decorin activates neuronal autophagy by increasing autophagosomal‐lysosomal degradation linking changes in ECM to autophagy.